Universal political scientist: the case of Oleg Borisovich Podvintsev - Kiryanov, I. K. (Perm Federal Research Centre Journal, 2025)
The article presents the contribution of Professor O.B. Podvintsev to the development of higher political science education and academic political science in Perm. In the complex compound of his interests, two key themes stand out for his comprehension of subnational politics in the modern world, i.e. the theme of post-imperial adaptation and the topic of elections, deep understanding of which was reflected in numerous research papers and original courses for students of the Faculty of History and Political science at Perm University. In connection with the second topic, he revealed himself not only as a theorist and apologist of psephology (the science of elections), but also as a successful political technologist.